Law Hill and Emily Brontë: Behind Charlotte's Evasion. (3rd July 2018) - Chitham, Edward
Abstract : This article aims to describe the experiences and development in confidence which Emily Brontë gained by her stay at Law Hill, which Charlotte suppressed. Various authors have suggested that this was a crucial period in her life. Hilda Marsden thought Wuthering Heights was 'born out of intense love for some special point of earth [Shibden and High Sunderland]'. Romer Wilson wrote, 'Something very serious befell Emily'. Ernest Raymond said, 'Emily may have experienced a passionate love' at Law Hill. The following matters will be considered in this article: (a) Emily's positive relations with some children and adults at Law Hill; (b) the educational practices and circle of acquaintance of the school's head; (c) the social background of the pupils, daughters of tradesmen, not the gentry; (d) a means by which Emily could visit High Sunderland; (e) Emily's only recorded adult friendship beyond her family. It also attempts to suggest why Charlotte airbrushed Law Hill from the record.